Quaternary ammonium nonanoate-based ionic liquids as chemicals for crop protection - Łęgosz, Bartosz; Biedziak, Agnieszka; Klejdysz, Tomasz; Pernak, Juliusz (European Journal of Chemistry, 2016)
The use of renewable chemicals has become one of the most rapidly developing trends in chemical synthesis. Numerous naturally occurring compounds become green alternatives for traditional oleochemicals due to the fact that they exhibit a wide range of attractive properties. Substances such as pelargonic (nonanoic) acid, which are obtained as secondary metabolites from plants or microorganisms, play a major role in their defense systems by protecting them from diseases, herbivores or predators. Therefore, due to their unique biological properties, the natural chemicals are potential components of ionic liquids (ILs). In this study, the synthesis and properties of ammonium ILs with nonanoate anion are presented. The reactions were conducted in a short time under ambient temperature and pressure. The products were obtained with high yields. The synthesized ILs were characterized by good surface active properties. Didecyldimethylammonium nonanoate reduced the surface tension of water to 21.86 mN/m. The feeding deterrence activity of the obtained nonanoates was also examined and the studied ILs exhibited high feeding deterrence activity, comparable to natural occurring antifeedants, azadirachtin. Additionally, the synthesized ILs were also active towards rods, cocci and fungi. The obtained results allowed to link surface properties with biological activity of synthesized ILs.